Critical Theory (of Law) from Latin American liberation thought - Sánchez Rubio, David (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2025)
This paper makes, from an iusphilosophical point of view, a connection between some ethical, axiological and evaluative contributions of Latin American liberation thought and critical theory in general, and the critical theory of law in particular. Three blocks are presented: a) an ecumenical anthropological faith based on a criterion of production, reproduction and development of human life; b) the categorical imperative against any process of victimisation; and c) finally, the proposal to denounce and confront the idolatrous processes and fetishisation of productions that juridically appear as an ideological inversion or reversal of human rights. The objective is to provide an input and material for analysis and orientation, in order to confront the current context of globalisation in the face of the various ontological dangers that threaten Humanity and planetary Nature.